New Paradigm of 21st Century Islamic Education - Nur, Muhammad Hajirin (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The new Rahmatan Lil' Alamin Islamic education approach offers a responsive and holistic paradigm. This paradigm places Islamic religious teachings as the primary basis for learning while connecting them with real-life contexts. Rahmatan Lil' Alamin Islamic Education strives for inclusion, where everyone has equal opportunities for quality education. This is supported by developing 21st-century skills, such as critical thinking, creativity, and collaboration. In addition, 21st-century Islamic education emphasizes the formation of sound and responsible character and respect for diversity and the environment. This new paradigm also integrates technology into the learning process, providing broader access and a richer learning experience for students. This study examines issues related to the new paradigm of 21st-century Islamic education using literature review research with a qualitative approach and descriptive-analytical methods. The conclusion, as well as the recommendation that the reconstruction of Islamic education and the application of the new paradigm of Rahmatan Lil 'Alamin, it is hoped that Islamic education can become a vehicle for forming individuals who have a noble character, have broad insight, and can face the challenges of the modern world.